Understanding expertise in burglars: From pre-conscious scanning to action and beyond. (January 2015) - Nee, Claire
Abstract: This article aims to review empirical research on residential burglary over the last three to four decades and relate these findings to a model of 'dysfunctional expertise' (Nee & Ward, this issue) that is rooted in mainstream cognitive psychology. It begins with a description of the elements of expertise that might fit in to this model and then traces the offender's decision-chain, using the model as an explanatory tool. Studies have shed light on: the automatic and habitual appraisal of the criminogenic environment during the daily, routine activities of the burglar and his journey to crime; accruing situational awareness and automatic recognition of cues signifying vulnerable properties during target selection; and speedy deployment of offending scripts based on tried and tested methods when entering and carrying out the crime. The review highlights how little is known about decisions, reflections and emotions after the crime. Aspects of the model that require development through further research, as well as the value of using the model for crime prevention purposes, are discussed.